Lipidomic insights into the immune response and pearl formation in transplanted pearl oyster Pinctada fucata martensii - Wu, Hailing; Yang, Chuangye; Hao, Ruijuan; Liao, Yongshan; Wang, Qingheng; Deng, Yuewen (Frontiers in Immunology, 2022)
During pearl culture, the excess immune responses may induce nucleus rejection and death of pearl oysters after transplantation. To better understand the immune response and pearl formation, lipidomic analysis was applied to investigate changes in the serum lipid profile of pearl oyster Pinctada fucata martensii following transplantation. In total, 296 lipid species were identified by absolute quantitation. During wound healing, the content of TG, and DG initially increased and then decreased after 3 days of transplantation with no significant differences, while the level of C22:6 decreased significantly on days 1 and 3. In the early stages of transplantation, sphingosine was upregulated, whereas PC and PUFAs were downregulated in transplanted pearl oyster. PI was upregulated during pearl sac development stages. GP and LC-PUFA levels were upregulated during pearl formation stage. In order to identify enriched metabolic pathways, pathway enrichment analysis was conducted. Five metabolic pathways were found significantly enriched, namely glycosylphosphatidylinositol-anchor biosynthesis, glycerophospholipid metabolism, alpha-linolenic acid metabolism, linoleic acid metabolism and arachidonic acid metabolism. Herein, results suggested that the lipids involved in immune response, pearl sac maturation, and pearl formation in the host pearl oyster after transplantation, which might lead to an improvement in the survival rate and pearl quality of transplanted pearl oyster.